2006
DOI: 10.1080/00015458.2006.11679833
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Results of Leg Amputation According to Ghormley’s Technique in the Treatment of Chronic Lower Limb Ischaemia

Abstract: The authors present their experience in the treatment of chronic lower limb ischaemia resulting from atherosclerosis by below knee amputation according to Ghormley's technique, with the immediate application of a semi-rigid plaster cast and early rehabilitation. From a group of 664 patients requiring major amputations, 61 patients (52 men) aged 64 +/- 11 fulfilled the criteria for unilateral below-knee amputation for critical limb ischaemia for atherosclerosis consequences. Peri-operative (30-days) mortality w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…[25][26][27][28] We also observed that the concomitant bilateral amputations were in accordance with other reports that stated values of 10.68% to 15%. 23,29 Previous studies 30,31 reported that failed BKA occurs in approximately 15% of patients, similar to the incidence observed in the present study. All new amputations to a more proximal level were performed in the BKA group.…”
Section: Discussionsupporting
confidence: 91%
“…[25][26][27][28] We also observed that the concomitant bilateral amputations were in accordance with other reports that stated values of 10.68% to 15%. 23,29 Previous studies 30,31 reported that failed BKA occurs in approximately 15% of patients, similar to the incidence observed in the present study. All new amputations to a more proximal level were performed in the BKA group.…”
Section: Discussionsupporting
confidence: 91%
“…www.efsupit.ro 1085 the tasks of prosthetics and training in the use of a prosthesis. At the same time, observations of a number of specialists suggest that effective rehabilitation of this contingent depends not only on qualitative prosthetics, but is largely provided by the level of adaptation of the basic systems of vital activity of the body (Kurdybailo, 2001;Wasiak, 2006;Wolthuis, 2006;Winell, 2006).…”
Section: Jpes ®mentioning
confidence: 99%
“…Due in part to the aging population and an increase in prevalence of those living with diabetes, the number of Americans with an amputation is projected to double by the year 2050 . Reported risk factors for affecting the presence and intensity of LBP that are unique to individuals with amputation include musculoskeletal imbalance secondary to altered gait mechanics and postural changes, deconditioning, poor prosthetic fit, leg‐length discrepancy, amputation level, multiple comorbidities, and presence of phantom limb or residual pain . Results are mixed; however, the majority of studies report that individuals with transfemoral amputation (TFA) tend to have a higher prevalence of LBP compared with those with transtibial amputation …”
Section: Introductionmentioning
confidence: 99%
“…8,11 Reported risk factors for affecting the presence and intensity of LBP that are unique to individuals with amputation include musculoskeletal imbalance secondary to altered gait mechanics and postural changes, deconditioning, poor prosthetic fit, leglength discrepancy, amputation level, multiple comorbidities, and presence of phantom limb or residual pain. [12][13][14][15][16][17] Results are mixed; however, the majority of studies report that individuals with transfemoral amputation (TFA) tend to have a higher prevalence of LBP compared with those with transtibial amputation. 1,2,4,5 Between 1996 and 2013, diabetes and the combination of low back and neck pain accounted for the first and third, respectively, highest health care spending in the United States and together were the conditions with the largest increase in health care spending over the 18-year period.…”
Section: Introductionmentioning
confidence: 99%